Microbiological, Physical and Chemical Assessment of Mineral Waters Sold in Vitória da Conquista - Gusmão, Isabel Celeste Caires Pereira (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
With the doubt on the quality of the water of public supplying, the citizen started to use the mineral water with bigger intensity. The objective of this research was to evaluate aspects of microbiological quality in natural mineral water samples, in individual bottles of two marks commercialized in the city of Vitória da Conquista. Ten samples proceeding from two marks had been used. The samples had been acquired randomly, at different times and establishments so that they were originated from diverse lots. For analysis of coliformes total and coliformes fecais/E. coli used it technique (NMP) determination of most likely number. For counting of heterotróficas bacteria, the technique of culture in depth was used. All the samples of all the marks (100%) had presented absence of coliformes fecais/E.coli seven samples (70%) of the two marks had presented 500 countings above of UFC/mL for heterotróficas bacteria presenting a disagreement in accordance with the Brazilian legislation for mineral waters that the limit of 500 establishes UFC/mL for water of human consumption proceeding from systems of public supplying.